PERSONAL BRANDING OF FREELANCE MAKE UP ARTIST (MUA) IN PEKANBARU CITY ON INSTAGRAM SOCIAL MEDIA - Suci Shinta Lestari; Mutia Farina (Jurnal Netnografi Komunikasi, 2025)
Searching for MUA services in the digital era is now easy, with many choices on social media such as Instagram, which allows searches based on domicile, price, characteristics or quality. This research aims to analyze the personal branding of freelance MUAs in Pekanbaru via Instagram, using Montoya's personal branding theory with eight indicators: specialization, leadership, personality, difference, visibility, unity, steadfastness and good name. The research subjects were four freelance MUAs in Pekanbaru, who were selected using snowball sampling techniques. The research results show that MUA uses testimonials, tutorials, and work results to build reputation, interact with audiences, and maintain activity on Instagram. Characteristics and educational abilities are key in personal branding, while steadfastness in facing industry challenges and maintaining a positive image is very important in maintaining professionalism.